2018
DOI: 10.3390/s18082546
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Systems to Train Psychomotor Skills in Hearing Impaired Children

Abstract: Objectives: The aim of this work is to provide a scoping review to compile and classify the systems helping train and enhance psychomotor skills in hearing impaired (HI) children. Methods: Based on an exhaustive review on psychomotor deficits in HI children, the procedure used to carry out a scoping review was: select keywords and identify synonyms, select databases and prepare the queries using keywords, analyze the quality of the works found using the PEDro Scale, classify the works based on psychomotor comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Additionally, hearing is closely related to movementhearing loss, language development and motor skills are fundamentally interdependent. The absence of internal speech and verbal support causes a delay in motor skill development, what is also shown in researches by Peñeñory [18]. The results reported in this study are in agreement with what has been found in previous studies examining psychomotor skills in the deaf [28,29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, hearing is closely related to movementhearing loss, language development and motor skills are fundamentally interdependent. The absence of internal speech and verbal support causes a delay in motor skill development, what is also shown in researches by Peñeñory [18]. The results reported in this study are in agreement with what has been found in previous studies examining psychomotor skills in the deaf [28,29].…”
Section: Discussionsupporting
confidence: 93%
“…Studies by a number of authors show that children with hearing loss differ in the following aspects of psychomotor development: -low level of motor skills [13]; -difficulties maintaining static and dynamic equilibrium [14,15]; -relatively low level of spatial orientation development [16]; -slow speed of performance of particular phases and tempos of movements [17]; -deviations in motor skills, which as a whole, characterize a low level of coordinative abilities [18]; -relatively low level of figurative thinking development due to a lack of internal speech and verbal support [19,20]. Effectively correcting the psychomotor development…”
mentioning
confidence: 99%
“…The optimal development of psychomotor skills and capacities, such as postural control, occurs during early childhood, and it is necessary, once in adulthood, for the attainment of the optimal cognitive and psycho-social functioning [ 1 ] and other more complex psychomotor abilities [ 2 ]. In early childhood, especially between 6 and 12 years of age [ 3 ], postural control develops and reorganizes permanently, adapting, through experience, to the constant growth of the body and to the incorporation and improvement of biomechanical strategies, such as anticipatory postural adjustments and alignment and balancing reactions [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In early stages of life, the balance has its own development with a strong reorganization at 6 years old [1]. This capacity depends on the senses (such as vision and proprioception), on vestibular system and the motor control system [2];which is necessary for the future cognition improvement, social interaction [3] and also other motor skills of great complexity for that range of age [4]. The experimental data demonstrate that, the first reference frame used for the organization of balance control during locomotion is the pelvis, especially in young children.…”
Section: Introductionmentioning
confidence: 99%